2021
DOI: 10.3390/life11070663
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Genomic Landscape: A Portrait of the Mitochondrial Genome 40 Years after the First Complete Sequence

Abstract: Notwithstanding the initial claims of general conservation, mitochondrial genomes are a largely heterogeneous set of organellar chromosomes which displays a bewildering diversity in terms of structure, architecture, gene content, and functionality. The mitochondrial genome is typically described as a single chromosome, yet many examples of multipartite genomes have been found (for example, among sponges and diplonemeans); the mitochondrial genome is typically depicted as circular, yet many linear genomes are k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 172 publications
(286 reference statements)
1
17
0
Order By: Relevance
“…These uORF elements have been identified in different fungal mitogenomes, and some may be shared among species, as recently demonstrated ( Fonseca et al, 2020 ; Araújo et al, 2021 ; Kulik et al, 2021 ), which suggests that uORFs within mitogenomes of fungi may play a significant role in shaping mitochondrial genome length. This is in agreement with a recent investigation of mitochondrial landscape in eukaryotes, which has found a positive correlation between mitochondrial genome length and the prevalence of unassigned regions ( Formaggioni et al, 2021 ). Nonetheless, differences in the literature suggest that there are probably inter-phyla variations.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…These uORF elements have been identified in different fungal mitogenomes, and some may be shared among species, as recently demonstrated ( Fonseca et al, 2020 ; Araújo et al, 2021 ; Kulik et al, 2021 ), which suggests that uORFs within mitogenomes of fungi may play a significant role in shaping mitochondrial genome length. This is in agreement with a recent investigation of mitochondrial landscape in eukaryotes, which has found a positive correlation between mitochondrial genome length and the prevalence of unassigned regions ( Formaggioni et al, 2021 ). Nonetheless, differences in the literature suggest that there are probably inter-phyla variations.…”
Section: Resultssupporting
confidence: 93%
“…Mitochondrial plasmids are widely found in Fungi and some mitochondrial genes, such as dpo and rpo , are commonly associated with plasmid integration events ( Formighieri et al, 2008 ; Férandon et al, 2013 ; Formaggioni et al, 2021 ). In our study, we identified dpo homologs in at least one species of six different phyla, with Basidiomycota and Ascomycota showing the highest numbers of sequences – 227 and 116, respectively ( Supplementary Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present Special Issue is an attempt to set and assess the state-of-art of mitochondrial genomics, with special reference to the suitability of mtDNAs for phylogenetic inference. The work by Formaggioni and colleagues [6] opens the Special Issue with a broad-scale analysis of the current knowledge on mitochondrial genomics, presenting the largest-to-date database of mtDNA features, which was made freely available to the scientific community. Similarly, the review by Parakatselaki and Ladoukakis [7], which closes the Special Issue, is specifically focused on mitochondrial heteroplasmy, a well-known phenomenon which is in fact neglected among the dogmatic "widespread" features of mitochondrial genomics, which include the strict maternal inheritance.…”
mentioning
confidence: 99%